Methodological bases of studying the dispersion composition of mine coal dust - Vladimir A. Rodionov (Вестник Пермского национального исследовательского политехнического университета. Геология. Нефтегазовое и горное дело, 2018)
The methodology of investigating the dispersion composition of mine dust is presented. The methodology is based on modern science-intensive methods such as the method of scanning microscopy and simple methods such as the method of sieve granulometric analysis. Today, the granulometric analysis is given great attention aimed to study the dimensions and aerodynamic characteristics of mine dust particles. The methods are applied separately from each other. Therefore, the paper discusses the most popular science methods gives recommendations on their joint application on the basis of the author's research on the dispersion composition of mine dust. Methods of scanning ectronic and optical microscopy are briefly described. Laser diffraction and sieve granulometric analyzes used to study the composition of coal mine dust are considered. That is chosen to use mine coal dust collected from the surface of hydraulic support racks of cleaning faces and coal dust obtained by the method of forced grinding of hard coal samples of different grades and anthracite as the samples for study. Samples of coal are taken from the working space of the mines of the Pechora, Kuznetsk and Donbass coal basins. Based on a comprehensive study of methods and analysis of results of studying the dispersion composition, their main advantages and disadvantages are given. The research methodology is based on physical methods for studying the dispersion characteristics of mine dust. In connection with the fact that one or another method is implemented in one device (installation), then in order to obtain complex data it is proposed to combine them into knowledge-intensive pairs. The combination in pairs of the equipment allows to study thoroughly both the dispersion composition and morphology of the dust particles, including the surface structure of dust particles if such a task is posed. Selection of samples and processes of preparing samples for research are in the basis of all methods used for obtaining qualitative and reliable scientific ...